Antibacterial activity of ten medicinal plants obtained from some selected villages in the states of Kedah and Penang, Malaysia - Abd. Samah, Othman; Zainol Abidin, Nurdiana (Fakultas Farmasi UGM, 2009)
The antimicrobial activities of ten plant extracts showed some degree of variation among Gram negative bacteria. Nineteen crude plant extracts were active against Gram positive bacteria as compared to only 9 against Gram negative bacteria. The most resistant bacteria was K.pneumoniae K6 which showed no sign of susceptibility towards any of the plant extracts. This might due to the presence of B-lactamase, which had been reported recently. S. epidermidis showed susceptibility towards all plants except from M. citrifolia L. the highest zone inhibition was 14.67 mm which was found in P. guajava extracts against S. epidermidis and this is closely followed by M. indica (at 13.67 mm) against the same bacteria. Among all the plants which havebeen studied only M. citrifolia L. extract did not show any sigh of antimicrobial activity. the result showed that means of inhibition zones between each plantextract were significantly different.